Information Wars Concepts in Present Social and Communication Technologies Realities - Hula, Ruslan; Perederii, Iryna; Vitrynska, Olena (International Journal of Engineering and Technology, 2018)
Present information wars concepts evolution tendencies in the global information space in the conditions of informational confrontation are revealed. Social and communication technologies functioning peculiarities in the information wars are considered. Information war transformation concepts modern tendencies in military theory are analyzed. Military-applied and psychological approaches interrelation with social and communicational technologies usage is analyzed.Â Â